2019
DOI: 10.3389/fbioe.2019.00193
|View full text |Cite
|
Sign up to set email alerts
|

Principal Component Analysis Reveals the Proximal to Distal Pattern in Vertical Jumping Is Governed by Two Functional Degrees of Freedom

Abstract: The successful completion of motor tasks requires effective control of multiple degrees of freedom (DOF), with adaptations occurring as a function of varying performance constraints. In this study we sought to compare the emergent coordination strategies employed in vertical jumping under different task constraints [countermovement jump (CMJ) with arm swing-CMJas and no arm swing-CMJnas]. In order to achieve this, principal component analysis (PCA) was conducted on joint moment waveform data from the hip, knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 64 publications
1
41
0
Order By: Relevance
“…In this study we found that the three-dimensional inter-segmental moments of 34 subjects performing a vertical jump can be represented by just 3 PCs. This is similar to our recent work where we showed that the sagittal plane inter-segmental moments during jumping could be described by 2 PCs [12]. It is notable here that only one further PC is required to capture 90% of the variance in the joint moments, despite the fact that the addition of the remaining two planes effectively triples the number of kinetic DOF in the input data.…”
Section: Figure 3 Mean Ground Reaction and Joint Contact Forces Durisupporting
confidence: 90%
See 1 more Smart Citation
“…In this study we found that the three-dimensional inter-segmental moments of 34 subjects performing a vertical jump can be represented by just 3 PCs. This is similar to our recent work where we showed that the sagittal plane inter-segmental moments during jumping could be described by 2 PCs [12]. It is notable here that only one further PC is required to capture 90% of the variance in the joint moments, despite the fact that the addition of the remaining two planes effectively triples the number of kinetic DOF in the input data.…”
Section: Figure 3 Mean Ground Reaction and Joint Contact Forces Durisupporting
confidence: 90%
“…One tool that is useful for this purpose is principal component analysis (PCA) a data reduction technique that can be used to establish the effective DOF present within a data set. We have recently employed PCA to demonstrate that the sagittal plane moments impressed by the lower limb during vertical jumping exhibit only 2 functional DOF [12]. The purpose of this study was therefore two-fold: firstly, to expand on our previous work by examining the moment production in all 3 dimensions, and secondly, to use PCA to evaluate the functional DOF present within the muscular control problem.…”
mentioning
confidence: 99%
“…It must also be acknowledged that the present study relies on investigation of joint kinematics at discrete time points (i.e., key instants). Future studies may therefore extend the current work using methodologies to investigate the continuous time series of kinematic data, such as statistical parametric mapping [40], vector coding [41] or principal component analysis [42], as well as considering other biomechanical principles not explored within this study. Additionally, differences in anthropometric data were not accounted for, where the same angular velocities and joint angles may lead to different linear velocities.…”
Section: Discussionmentioning
confidence: 99%
“…This raw data was used to calculate the knee joint moments generated by each participant during the vertical jump using a publicly available model of the lower limb (Cleather and Bull, 2015). A detailed description of the processing of this data is provided in Cushion et al (2019). To facilitate comparison of different time-series the data was time-normalised.…”
Section: Methodsmentioning
confidence: 99%